Complications and competing risks of death in compensated viral cirrhosis (ANRS CO12 CirVir prospective cohort). Issue 3 (20th March 2015) - Trinchet, Jean‐Claude; Bourcier, Valérie; Chaffaut, Cendrine; Ait Ahmed, Mohand; Allam, Setty; Marcellin, Patrick; Guyader, Dominique; Pol, Stanislas; Larrey, Dominique; De Lédinghen, Victor; Ouzan, Denis; Zoulim, Fabien; et al.
<x xml:space="preserve">Abstract</x> Various critical events, liver related or not, occur in patients with compensated cirrhosis, but their respective burden remains to be prospectively assessed. The aim of this prospective cohort study involving 35 French centers was to capture the whole spectrum of complications occurring in compensated viral cirrhosis (VC) using competing risks analyses. Inclusion criteria were: histologically proven cirrhosis resulting from hepatitis C virus (HCV) or hepatitis B virus (HBV); Child‐Pugh A; and no previous hepatic complications. The cohort was considered as a multistate disease model, cumulative incidences (CumIs) of events were estimated in a competing risks framework. A total of 1, 654 patients were enrolled from 2006 to 2012 (HCV, 1, 308; HBV, 315; HCV‐HBV, 31). During a median follow‐up of 34 months, at least one liver nodule was detected in 271 patients, confirmed as hepatocellular carcinoma (HCC) in 128 (4‐year cumI: 10.5%) and cholangiocarcinoma in 3. HCC incidence was higher in HCV (4‐year cumI: 11.4% vs. 7.4%; P = 0.05). HCC fulfilled Milan criteria in 79.3%, leading to curative treatment in 70.4%. Liver decompensation occurred more frequently in HCV patients (4‐year cumI: 10.8% vs. 3.6%; P = 0.0004). Virological eradication/control was achieved in 34.1% of HCV and 88.6% of HBV patients and was associated with a marked decrease in HCC, decompensation, and bacterial infection incidences. Survival was shorter in HCV patients (4‐year cumI: 91.6% vs. 97.2%; P = 0.0002). Death (n = 102; missing data: 6) was attributed to liver disease in 48 (47%; liver cancer: n = 18; miscellaneous, n = 30) and extrahepatic causes in 48 (47%; bacterial infection: n = 13; extrahepatic cancers: n = 10; cardiovascular events: n = 5; miscellaneous, n = 20). Conclusion: After 3 years of follow‐up, extrahepatic events still explained half of deaths in patients with compensated VC. A strong decrease in complications was linked to virological eradication/control. (Hepatology 2015;62:737–750)